Climate Change and Challenges of Water and Food Security to Smallholder Farmers of Madhya Pradesh: An Overview (Agro-Science Letters, 2026)
Projections suggest that nearly three-quarters of Himalayan glaciers  will have retreated substantially by 2035. Additionally, a reduction in  precipitation of approximately 10% is anticipated in Uttar Pradesh, India by  2050, potentially diminishing river drainage by 17%. Freshwater reserves are  being depleted at an alarming rate, while expanding global populations and  food requirements are eroding agricultural productivity worldwide. How  well agriculture adapts to climate change will largely determine the future  availability of food globally. India faces mounting challenges, including  increasingly frequent droughts, intense flooding events, erratic monsoon  patterns, and declining crop production linked to global climate change.  Urbanization, rapid industrialization, and growing demands for irrigation  water are placing extraordinary pressure on existing water resources. Land  degradation is directly linked to rising global temperatures, with roughly  130 million hectares (mha) of Indian land showing various degrees of  deterioration — encompassing 32.8 mha affected by water erosion, 10.8  mha by wind erosion, 8.5 mha by desertification, and a further 8.5 mha by  waterlogging. This study identifies practical and cost-effective approaches  to safeguarding food and water security under a changing climate, while  recommending robust adaptation and mitigation strategies to reduce climate  change impacts on irrigation and water resource systems.
Keywords: Climate change; irrigation; water and food security; smallholder farmers